Ambiguitas Agama sebagai Peluang dalam Menciptakan Perdamaian Agama - Fauzi, Ihsan Ali (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2015)
Popular news on religious issues tends to simplify the values of religion in socio-political expressions. They attend to blow acts of violence up in the name of religion. In this context, media remark some religious groups by using horrible terms and idioms, such as zealots, extremists, militants, etc. Moreover, they swipe it with taking some appalling photos and pictures. Religious leaders perceive this phenomenon as kind of misunderstanding paradigm in approaching and viewing religion, having known that conflict and violence are not only socio-political expression of religion. There are many untold beautiful expressions of religion, like Mahatma Gandhi, Martin Luther King, Mother Theresa, Malcolm X, and Dalai Lama. This article attempts to explore how religion can deeply be embodied with peace building, conflict management, and peace studies. It suggests that in order to be a tool of peace building, religion should not be used for proselytizing other people but rather should be put in academic and rational way to spread voices of peace. In addition to this, peace message of religion should also be expressed especially in social media as a counteraction against violent message of religious extremists. And the last thing is that peace building can only be achieved when peace work can bridge religious and secular communities.